Dificuldades na mobilidade para pessoas idosas em farmácias: uma análise do ponto de vista de acessibilidade - Silva, Luiz Gustavo Souza Da [UNESP]; Barbieri, Fabio Augusto [UNESP]; Strabeli, Giovana Innocenti; Silva, João Carlos Riccó Plácido Da; Paschoarelli, Luis Carlos [UNESP] (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2025)
Older adults may experience mobility limitations, which increase their risk of falls. Pharmacies, frequently visited by the elderly, may not provide adequate accessibility, further raising these risks. This study analyzed the factors affecting the mobility of older adults in pharmacies based on the NBR 9050/2020 standard. Three establishments were evaluated using the walkthrough methodology. Technical plans were developed from video recordings to verify key compliance points with the standard. The results revealed non-conformities, such as inadequate circulation with obstacles like boxes, carpets, and structural elements, as well as insufficient width, in addition to elevated display areas posing potential risks. One of the locations had stairs and ramps without handrails, violating the standard. These accessibility limitations in the environment hinder elderly mobility and increase the risk of imbalance, tripping, and falls. In conclusion, beyond improving accessibility, mobility, and safety in pharmacies, it is essential that design professionals and public authorities strictly adhere to technical standards, alongside new specific knowledge, to ensure the social participation of older adults in public spaces.

Idosos podem apresentar limitações quanto à mobilidade, o que os expõe a um maior número de quedas. As farmácias, locais constantemente visitados por idosos, podem não apresentar uma acessibilidade adequada, ampliando os riscos. Este estudo analisou os fatores que afetam a mobilidade de pessoas idosas em farmácias com base na norma NBR 9050/2020. Três estabelecimentos foram avaliados, utilizando a metodologia walkthrough. Plantas técnicas foram elaboradas a partir de registros de vídeo para verificar os principais pontos da norma. Os resultados evidenciam inconformidades,tais como: circulação inadequada com obstáculos, como caixas, tapetes e partes estruturais; falta de largura mínima, além de áreas de exposição elevadas que oferecem potenciais riscos. Um dos locais apresentou escadas e rampas sem corrimão, contrariando a norma. Essas limitações na acessibilidade nos ambientes dificultam a mobilidade de idosos e aumentam o risco de desequilíbrio, tropeços e quedas. Em conclusão, além de melhorar a acessibilidade, mobilidade e segurança nas farmácias, é essencial que profissionais de projeto e autoridades públicas sigam rigorosamente as normas técnicas, associadas aos novos conhecimentos específicos, para garantir a participação social dos idosos em ambientes públicos.
Mobility difficulties for older people in pharmacies: an analysis from the point of view of accessibility
Keywords: Accessibility; Locomotin; Ergonomics; Built Spaces; Pharmacies; Aging; Acessibilidade; Locomoção; Ergonomia; Espaços construídos; Farmácias; Envelhecimento